Integrated thermal and phytoremediation of agricultural soils impacted by PFAS - Jake T. Thompson; Millie Dobson; Tim Jesper Suhrhoff; Yoshiki Kanzaki; Chloe Kent; Lucinda Bryce; Ella Milliken; Christopher T. Reinhard; Yuan Yao; Noah Planavsky (Proceedings of the National Academy of Sciences, 2026)
Per- and polyfluoroalkyl substances (PFAS) are persistent synthetic compounds that have contaminated millions of hectares of agricultural land through decades of biosolids application. Conventional remediation approaches, such as thermal destruction or excavation, are prohibitively expensive, carbon intensive, and leave affected farmland unfit for agriculture. Here, we present a potential scalable remediation strategy that combines phytoremediation, biochar production, and enhanced weathering to simultaneously remove PFAS from soil, immobilize residual contamination, and achieve durable carbon dioxide removal (CDR). Using stochastic modeling constrained by experimental data, we show that soil pH management through alkaline rock amendment can accelerate PFOS removal, shortening remediation timelines by more than a decade under typical contamination levels. Pyrolysis of harvested biomass effectively destroys PFAS and produces biochar, which, when reapplied to soil, substantially reduces leaching to groundwater and the surrounding environment. National-scale simulations across the estimated one million hectares of PFAS-impacted cropland indicate a combined CDR potential of approximately 11 Mt CO 2 y –1 , equivalent to 4 to 6% of the US 2050 carbon removal target. We estimate a median remediation cost of $1,460 USD ha –1 y –1 —more than an order of magnitude lower than current technologies, with costs substantially reduced through carbon removal revenues valued near the social cost of carbon. This integrated thermal and phytoremediation framework provides a viable pathway to restore contaminated farmland, mitigate PFAS exposure risks, and contribute meaningfully to national climate mitigation goals.